The Influence of Compensation and Workload on the Quality of Health Services in Hospitals with the Effectiveness of Electronic Medical Records as a Mediating Variable - Mugi Rahayu Pangestuti; Yusuf Alam Romadhon; Rini Kuswati (International Journal of Management Science and Information Technology, 2024)
The aim of this research is to analyze the influence of compensation and workload on the quality of health services in hospitals with the effectiveness of electronic medical records as a mediating variable. This research method is quantitative. The population in this study were General Practitioners, Nurses, and Midwives at AN-NISA Tangerang Hospital. The sampling technique in this research uses a saturated sample technique. The number of respondents in this study was 302 respondents. This research uses primary data in its preparation. The data collection method used in this research was by distributing questionnaires. The data analysis technique in this research uses Partial Least Square (PLS) with the help of SMARTPLS Software. The results of this research are that compensation does not have a significant influence on service quality. Workload has a positive and significant influence on Service Quality. Compensation has a positive and significant influence on the effectiveness of electronic medical records. Workload has a positive and significant influence on the effectiveness of electronic medical records. The effectiveness of Electronic Medical Records has a positive and significant influence on Service Quality. The calculation results show that the effectiveness of electronic medical records can mediate the influence of compensation on service quality. The calculation results show that the effectiveness of electronic medical records can mediate the influence of workload on service quality.